Comportamento tribológico da liga Inconel 718 nitretada por plasma em gaiola catódica - Oikava, Yukyhiro Inomata (2019)
Nickel-based superalloys, such as Inconel 718, are widely used in the oil and gas industry to comply technical design requirements due to the application conditions. Even with suit corrosion resistance the Inconel 718 alloy may have limited applications due to its relatively low hardness with consequent improper wear resistance. One alternative for this problem to be solved is through the plasma assisted nitriding process. In this work a comparative study was carried out to compare the tribological behavior of thermochemically treated surfaces submerged in saline solution. The present study settled the critical load between a 2 N to 8 N applying variable load at linear scratch test of the Inconel 718 alloy, which was treated by Active Screen Plasma Nitriding (ASPN). The surfaces were characterized by XRD (X-Ray Diffraction), Vickers microhardness measurement, 3D optical interferometry, in addition to the optical microscope and SEM (Scanning electron microscopy). The properties of the surface were verified as per hardness and roughness, while the tribological behavior was obtained by means of the ball-on-plane configuration, in reciprocating motion, evaluating the coefficient of friction, volume and wear mechanisms. Two materials were used as counterbody, these being a bearing steel and silicon nitride. Through the linear scratch test with variable load applied, it was possible to set the maximum load of 5 N, corresponding to the beginning of the failure on the treated surface. The nitriding treatment promoted an increase at the abrasion resistance on Inconel 718 substrate. The counterbodies influenced straight on tribological behavior of the tested tribosystems, especially at the wear mechanisms observed for the nitrided and untreated specimens. The tribosystem which presented lower coefficient of friction and less wear was composed by the steel sphere sliding on the nitrided surface. The oxide layer meet conditions to behave as a protective and lubricant interface, in combination with the highest surface hardness after plasma nitriding treatment. When the silicon nitride sphere was used as against body, the abrasion mechanism was predominant, even eliminating the beneficial effect of the nitrided layer on the surface, both in the friction, as well as in the worn volume.